Novel 1,2,4-triazole substituted metallo-phthalocyanines: Synthesis, characterization and investigation of electrochemical and spectroelectrochemical properties - KOCA, ATIF (ELSEVIER SCIENCE BV, 2018)
The phthalonitrile compound (3) and peripherally tetra substituted zinc(II) (4), nickel (II) (5), iron (II) (6), cobalt (II) (7) and copper (II) (8) phthalocyanines were synthesized for the first time in this study. The structural characterization of these novel compounds were performed with FT-IR, H-1 NMR, C-13 NMR, UV-Vis and mass spectroscopy. The redox properties of the complexes were investigated by cyclic voltammetry, square wave voltammetry, controlled-potential coulometry and in-situ spectroelectrochemistry. The effects of redox active and inactive metal centers on the electrochemistry of 4-2-(4-methyl-5-phenyl-4H-1,2,4-triazol-3-ylthio)ethoxy substitute phthalocyanine were examined. The color changes associated with the redox processes and electro-generated anionic and cationic redox species were suggested their applicability in the fields of the electrochemical technologies. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Phthalocyanine; [1,2,4] triazole; Electrochemistry; Spectroelectrochemistry; ZINC(II); COBALT; TETRA; METALLOPHTHALOCYANINES; DERIVATIVES; MANGANESE; NICKEL; CO(II); COPPER; ALPHA